High-pressure reactions between the pnictogens: the rediscovery of BiN - Glazyrin, K.; Aslandukov, A.; Aslandukova, A.; Fedotenko, T.; Khandarkhaeva, S.; Laniel, D.; Bykov, M.; Dubrovinsky, L. (Frontiers in Chemistry, 2023)
We explore chemical reactions within the pnictogens with an example of bismuth and nitrogen under extreme conditions. Understanding chemical reactions between Bi and N, elements representing the first and the last stable elements of the nitrogen group, and the physical properties of their compounds under ambient and high pressure, is far from being complete. Here we report the high-pressure high-temperature synthesis of orthorhombic Pbcn BiN (S.G. #60) from Bi and N2 precursors at pressures above 40 GPa. Using synchrotron single crystal X-ray diffraction on the polycrystalline sample, we solved and refined the compound’s structure and studied its behavior and compressibility on decompression to ambient pressure. We confirm the stability of Pbcn BiN to pressures as low as 12.5(4) GPa. Below that pressure value, a group-subgroup phase transformation occurs resulting in the formation of a non-centrosymmetric BiN solid with space group Pca21 (S.G. #29). We use ab-initio calculations to characterize the polymorphs of BiN. They also provide support and explanation of our experimental observations, in particular those corresponding to peculiar Bi-N bond evolution under pressure resulting in a change of the coordination number of Bi and N as a function of pressure within the explored stability field of Pbcn BiN